Discovery on Antibiotic Resistance Patterns of Vibrio parahaemolyticus in Selangor Reveals Carbapenemase Producing Vibrio parahaemolyticus in Marine and Freshwater Fish - Lee, Learn-Han; Ab Mutalib, Nurul-Syakima; Law, Jodi Woan-Fei; Wong, Sunny Hei; Letchumanan, Vengadesh (Frontiers in Microbiology, 2018)
Vibrio parahaemolyticus, a Gram-negative halophilic bacterium is often associated with fish and fishery products, thus causing gastroenteritis in humans upon ingestion of contaminated food. V. parahaemolyticus has become a globally well-known pathogen with yearly reported cases in many countries. This study aimed to discover the antibiotic resistance patterns of V. parahaemolyticus as well as detect Carbapenem resistant isolates from marine and freshwater fish in Selangor. A total of 240 freshwater and marine fish samples collected from wetmarket and supermarket in Selangor were tested for the presence of V. parahaemolyticus. All the fish samples were determined positive for V. parahaemolyticus using conventional microbiological culture-based method. The toxR gene were detected via polymerase chain reaction (PCR) in 165/240 (69%) isolates. The two-virulence factor of V. parahaemolyticus, thermostable direct hemolysin (tdh) and TDH-related hemolysin (trh) was screened via PCR. As such, four isolates were trh + and none were tdh +. Majority of the isolates presented high resistance to ampicillin (88%), amikacin (64%), and kanamycin (50%). In addition, this study identified 19-imipenem resistant isolates isolated from freshwater and marine fish samples. Further analysis of these 19-imipenem resistant isolates revealed that the resistance towards imipenem was plasmid mediated after plasmid curing assay. The multiple antibiotics resistance index was >0.2 for 70% of the isolates. In summary, the results confirm the presence of V. parahaemolyticus in freshwater and marine fish samples in Selangor, Malaysia. To our best knowledge, this is the first report discovering the antibiotic resistant patterns and Carbapenem-resistant isolates of V. parahaemolyticus isolated from marine and freshwater fish samples in Selangor.